MAKING AUGMENTED REALITY (AR) BASED CHEMANJI LEARNING GAME ON MOLECULAR GEOMETRY CONCEPT - Vina Malihah; Ida Farida; Sari Sari (Gunung Djati Conference Series, 2021)
Chemistry requires the ability to understand macroscopic, submicroscopic and symbolic phenomena. However, the lack of a strategy to understand the concept at the submicroscopic level has resulted in an incomplete understanding of the concept of chemistry. This is due to the limited tools that can provide visualization of abstract concepts.The use of the Chemanji game board that collaborates with AR technology is expected to be able to visualize the concept of the macroscopic, symbolic and submicroscopic levels and cultivate character in competitive and collaborative team type play. The purpose of this study was to analyze the results of the validation test and describe the appearance of the product of the Chemanji learning game based on Augmented Reality (AR) on the molecular geometry concept. The research method used is Design Based Research (DBR) which is used to describe the appearance of Chemanji learning games based AR through flowcharts, storyboards and validation tests using validation sheets. The results of the Chemanji learning game based on Augmented Reality (AR) have an average value was 0.89 which indicates that chemanji learning games AR-based are valid and can be used as a learning media that is effectively used in learning.